Understanding Neuronal Architecture in Obesity through Analysis of White Matter Connection Strength - Riederer, Justin W.; Shott, Megan E.; Deguzman, Marisa; Pryor, Tamara L.; Frank, Guido K. W. (Frontiers in Human Neuroscience, 2016)
Despite the prevalence of obesity, our understanding of its neurobiological underpinnings is insufficient. Diffusion weighted imaging and calculation of white matter connection strength are methods to describe the architecture of anatomical white matter tracts. This study aimed to characterize white matter architecture within taste-reward circuitry in a population of obese individuals. Obese (n=18, age = 28.7 ± 8.3 years) and healthy control (n=24, age = 27.4 ± 6.3 years) women underwent diffusion weighted imaging. Using probabilistic fiber tractography (FSL PROBTRACKX2 toolbox) we calculated connection strength within 138 anatomical white matter tracts. Obese women displayed lower and greater connectivity within taste-reward circuitry compared to controls (Wilks’ λ < 0.001; p < 0.001). Connectivity was lower in white matter tracts connecting insula, amygdala, prefrontal cortex, orbitofrontal cortex and striatum. Connectivity was greater between the amygdala and anterior cingulate cortex. This study indicates that lower white matter connectivity within white matter tracts of insula-fronto-striatal taste-reward circuitry are associated with obesity as well as greater connectivity within white matter tracts connecting the amygdala and anterior cingulate cortex. The specificity of regions suggests sensory integration and reward processing are key associations that are altered in and might contribute to obesity.